Effect of aqueous extracts of quinoa mojuelo (Chenopodium quinoa Willd.) on arupo plants (Chionanthus pubescens Kunth) - Castro-Albán, Hugo Alejandro (2025)
Introduction. Chionanthus pubescens Kunth is an endemic tree of southern Ecuador with ornamental uses in the villages of the region due to its pink inflorescence. Objective. To evaluate the effect of aqueous extracts of quinoa mojuelo (Chenopodium quinoa Willd.) on the growth of arupo plants (Chionanthus pubescens Kunth) and the incidence of Fusarium sp. Materials and methods. The trial was conducted in the province of Chimborazo, Ecuador, during 2022. Aqueous extracts of quinoa mojuelo were obtained using the Soxhlet method, and their concentrations were determined by UV-VIS spectrophotometry. A completely randomized block design with a bifactorial arrangement was used, with three levels for factor A (aqueous extract of mojuelo: mother extract at 100%, and 50 % and 75 % dilutions in sterile distilled water; v/v) and three levels for factor B (application frequency: every 7, 14, and 21 days). Ten treatments were evaluated, including an absolute control, with three repetitions each. In ten randomly selected plants per treatment, morphological variables (height, number of leaves per plant, and stem diameter) were measured, as well as the incidence of Fusarium sp. Results. The 50 % and 75 % aqueous extract concentrations applied weekly promoted better morphological development and reduced the percentage of Fusarium sp. incidence in arupo plants, as reflected in height (16.3 cm), number of leaves (17.8), stem diameter (6.5 cm), and disease incidence (50 %). Conclusions. Aqueous extracts obtained from quinoa mojuelo applied to Chionanthuspubescens Kunth plants in nursery conditions reduced the incidence of Fusarium wilt and favored their growth in the early stages of development.